STATE OF THE PROBLEM OF CHILD DISABILITY IN OPHTHALMOPATHOLOGY IN THE STAVROPOL TERRITORY - Olga Sergeevna Zavodnova; Irina Leonidovna Lisovskaya; Olga Viktorovna Maletskaya (Вестник Северо-Кавказского федерального университета)
Conducted a retrospective analysis of the level of disability of vision in children up to 18 years of age in the Stavropol territory. The analysis of age structure showed that the highest percentage of children newly recognized disabled by impaired (from 59,34 to 63,6%) was observed in the age group from 0 to 7 years. Increased share of persons with ophthalmopathology in the structure of these.